Industrial training report: Maybank Berhad / Muhammad Affandy Baharuddin Shah - Baharuddin Shah, Muhammad Affandy (Bachelor of Information Science (HONS.) Records Management, 2015)
Maybank is one of the famous and top banking industries in Asia. It is known because it is the largest bank and financial group in Malaysia, with significant banking operations in Singapore, Indonesia and the Philippines. During the six months of my internship program, I have capture and adapt many skills such as management, data analysis, human resource job and many more. The department that I am being attached played a very important role in dealing with the staffs in Maybank. This department role is to make any action in dealing with transfer of staff, attrition or resignation of staff and also make a confirmation on promotion and renewal of contract of staff. In human capital management, organizations treat their employees as important resources that play an instrumental role in productivity of the organization. The development and management of individuals in line with their key responsibility areas not only make them a crucial resource in the future but also ensure their hundred percent contributions towards the organization. BMELP are one of the programme that Maybank provide for newly fresh graduated student across Malaysia. I was engage with this programme to handle and manage their 3 years attachment and on-going assessment.